IFC Mobile Money Study 2011 : Summary Report - International Finance Corporation (Washington, DC, 2015)
Mobile money (m-money) refers to the use of mobile phones to perform financial and banking functions. However, the technology is far ahead of the infrastructure of financial and technical network service providers needed for an m-money system to function. This study was undertaken to increase the understanding of m-money and to address key issues in scaling up development of m-money services globally. It examines the potential demand for m-money, national regulatory environments, major obstacles, and the requirements of potential service providers and networks to run m-money services as viable businesses. Four countries - Brazil, Nigeria, Sri Lanka, and Thailand - each of which represents a different world region, socioeconomic situation, and financial sector context, were included in the study. The countries were analyzed in terms of m-money business models, money flows and demand, potential user perceptions and behavior, regulations, and agent networks. In each country, an m-money service provider acted as a partner institution. To place these four countries in the wider context of m-money developments, three case studies - Japan, Kenya, and the United States were also examined. The size of potential opportunities for m-money were quantified through demand estimates and compared with estimates in the three reference countries. Chapter one provides an introduction to the study's objectives and context, and explains the definition and positioning of m-money used in this report. Chapter two presents case studies of the prominent m-money countries Kenya and Japan, as well as the United States. Chapter three presents an overview of the four country study findings and analysis. Chapter four describes the m-money business models adopted in each country and the challenges that each country faces. Chapter five concludes by placing each country along an m-money demand curve and explains the impact of this placement on the development of an opportunity for m-money.